Oncolytic viral gene therapy in ovarian cancer - McNeish,IA (2011)
Oncolytic viruses are a novel treatment for cancer. These agents infect cancer cells and replicate selectively within them, causing death with release of mature virions that can subsequently infect neighbouring cells. A series of viruses have been developed and are being taken towards clinical trials in women with relapsed ovarian cancer. However, the majority of data derive from research on adenoviruses. In this chapter, I review the biology of adenoviruses, clinical trials of oncolytic viral gene therapy in ovarian cancer and recent developments that may give cause for cautious optimism.Successful completion ofany DNA virus life cycle requires the virus to overcome many cellular pathways and checkpoints in order to permit replication of the viral DNA and generation of new virions. Many of the pathways targeted by DNA viruses are the same as those deregulated in cancer and it is this overlap between virus and cancer biology that makes replicating viruses potential treatments for human malignancy.The first description of viruses as anti-cancer agents came over 100 years ago and, in 1953, a clinical trial to investigate the therapeutic potential of adenoviruses was conducted in women with cervical cancer and some short-lived responses were seen. More recently, there have been anecdotal descriptions of lymphoma regressing following measles infection.